Legal Service Post Application at the Soppeng District Attorney Office - Ihsanulfu’ad Suwandi; Zul Rachmat (Formosa Journal of Science and Technology, 2022)
With the development of technology, it makes work faster and more efficient, such as in legal services or the provision of legal services by the State Attorney (JPN) in writing or orally to the public, which includes individuals and legal entities as well as legal service posts. However, with the habit of people coming to the office to carry out consultations which take time for services, this prompted us to create a Web-Based Legal Service Post Application at the Soppeng District Attorney's Office. With the waterfall research method in application design there is analysis, design, implementation, testing and maintenance so as to produce a Web-Based Legal Service Post Application that can facilitate the community and prosecutor's staff in the legal service process so that this activity can be carried out without having to go directly to the office.